Adaptation and Transcriptome Analysis of Aureobasidium pullulans in Corncob Hydrolysate for Increased Inhibitor Tolerance to Malic Acid Production - Zou, Xiang (PLoS One, 2015)
Malic acid is a dicarboxylic acid widely used in the food industry, and is also a potential C4 platform chemical. Corncob is a low-cost renewable feedstock from agricultural industry. However, side-reaction products (furfural, 5-hydroxymethylfurfural (HMF), formic acid, and acetic acid) that severely hinder fermentation are formed during corncob pretreatment. The process for producing malic acid from a hydrolysate of corncob was investigated with a polymalic acid (PMA)-producing Aureobasidium pullulans strain. Under the optimal hydrolysate sugar concentration 110 g/L, A. pullulans was further adapted in an aerobic fibrous bed bioreactor (AFBB) by gradually increasing the sugar concentration of hydrolysate. After nine batches of fermentation, the production and productivity of malic acid reached 38.6 g/L and 0.4 g/L h, respectively, which was higher than that in the first batch (27.6 g/L and 0.29 g/L h, respectively). The adapted strain could grow under the stress of 0.5 g/L furfural, 3 g/L HMF, 2g/L acetic acid, and 0.5 g/L formic acid, whereas the wild type did not. Transcriptome analysis revealed that the differentially expressed genes were related to carbohydrate transport and metabolism, lipid transport and metabolism, signal transduction mechanism, redox metabolism, and energy production and conversion under 0.5 g/L furfural and 3 g/L HMF stress conditions. In total, 42 genes in the adapted strain were upregulated by 15-fold or more, and qRT-PCR also confirmed that the expression levels of key genes (i.e. SIR, GSS, CYS, and GSR) involved in sulfur assimilation pathway were upregulated by over 10-fold in adapted strain for cellular protection against oxidative stress.